Картографування рівнинних лісів України на основі щільних часових рядів супутникових знімків Landsat - Миронюк, Віктор; Myroniuk, Viktor (Видавництво Львівської політехніки, 2019)
У дослідженні опрацьовано фенологічно орієнтований метод дешифрування вкритих лісовою рослинністю ділянок на території рівнинної частини України, використовуючи часові ряди супутникових знімків Landsat 8 OLI. Класифікацію знімків виконано за алгоритмом Random Forest в «хмарній» платформі Google Earth Engine API. У результаті створено лісову маску рівнинних лісів України з просторовим розрізненням 30 м. Її точність за показниками точності користувача (user’s accuracy) та виробника (producer’s accuracy) в середньому оцінюється на рівні відповідно 0,795±0,022 та 0,845±0,025. При цьому для поліської частини регіону дослідження точність виявилася вищою, а степової зони – навпаки, нижчою.

The paper discuses phenology-based method of mapping forested areas of flatland Ukraine using time series of Landsat 8 OLI images. The study is based on 1548 scenes of images that have been composed in four seasonal mosaics: yearly, summer, autumn, AprilOctober. The classification has been performed by Random Forest algorithm in Google Earth Engine API cloudbased platform. In total, 36 spectral features of seasonal mosaics were used in the study. About 4700 random points have been visually interpreted by Google images and used as a reference dataset. After classification, the forest mask of flatland Ukraine have been created having 30 m spatial resolution. In average, user’s and producer’s accuracies is assessed to be 0,795±0,022 and 0,845±0,025 respectively, although the forest mask is more accurate for Polissia regions and lower – for Steppe zone.
Mapping flat land forests of Ukraine using dense time series of Landsat satellite images
Keywords: лісова маска; лісистість; «хмарні» обчислення; Google Earth Engine; forest mask; forest cover; cloud computations; Google Earth Engine; 630*53